2012
DOI: 10.3109/0886022x.2012.668741
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio as a Predictor of Worsening Renal Function in Diabetic Patients (3-Year Follow-Up Study)

Abstract: Background: Previous studies have demonstrated the role of inflammation in diabetic nephropathy (DN). Neutrophil to lymphocyte ratio (NLR) rather than other white cell parameters was found to be a useful inflammatory marker to predict adverse outcomes in medical and surgical conditions. Nevertheless, the value of NLR in predicting DN has not been elucidated. Method: An observational study included 338 diabetic patients, who were followed at our clinic between 2007 and 2009. We arranged our patients into tertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 44 publications
(48 reference statements)
4
78
2
3
Order By: Relevance
“…In terms of medical comorbidities, there was no significant difference in preoperative NLR values between patients with low or high ASA scores; however, worse preoperative renal function was associated with higher preoperative NLR. This latter association is in concordance with the medical literature and reflects the systemic inflammatory response with renal failure [21][22][23].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In terms of medical comorbidities, there was no significant difference in preoperative NLR values between patients with low or high ASA scores; however, worse preoperative renal function was associated with higher preoperative NLR. This latter association is in concordance with the medical literature and reflects the systemic inflammatory response with renal failure [21][22][23].…”
Section: Discussionsupporting
confidence: 73%
“…The easily calculated NLR, on the other hand, has shown utility as an alternative marker of systemic inflammation in critically ill patients [19], malignancies [20], and chronic medical conditions such as end-stage renal disease and diabetes [21][22][23]. Our study's goal was to determine whether preoperative NLR can be incorporated in preoperative decision making for patients with small renal masses, as 20% of those masses prove benign after surgery [24].…”
Section: Discussionmentioning
confidence: 99%
“…One review article also indicated that NLR has been related to arterial stiffness and high coronary calcium scores, which are significant markers of CVD (34). Recently, NLR has been reported to be a prognostic marker for outcomes that result from diabetic retinopathy (35), including microvascular complications (36) and impaired renal function (37). Although the precise mechanisms that underlie the associations between systemic inflammation and prevalent conditions remain to be elucidated, these studies verify the present conclusion that NLR could be used as an innovative and effective predictor for T2D.…”
Section: Discussionmentioning
confidence: 99%
“…Bulgular: Hasta grubunda ölçülen serum leptin düzeyi control grubundan istatistiksel olarak anlamlı yüksek bulundu (1624.88±1608. 16 and 416±439.85). Hesaplanan peritonit insidansı 0.041±0.047 peritoniti/ hasta yılı olarak bulundu.…”
Section: öZetunclassified